2020
DOI: 10.3390/cells9030683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glycosylated PTGS2 in Colorectal Cancer for NSAIDS-Based Adjuvant Therapy

Abstract: Observational/retrospective studies indicate that prostaglandin-endoperoxide synthase-2 (PTGS2) inhibitors could positively affect colorectal cancer (CRC) patients’ survival after diagnosis. To obtain an acceptable cost/benefit balance, the inclusion of PTGS2 inhibitors in the adjuvant setting needs a selective criterion. We quantified the 72 kDa, CRC-associated, glycosylated form of PTGS2 in 100 frozen CRC specimens and evaluated PTGS2 localization by IHC in the same tumors, scoring tumor epithelial-derived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Song et al [ 31 ] showed that reducing PTGS2 expression can help to reduce the occurrence of colorectal cancer. This possibility is consistent with the results presented by Venè et al [ 32 ], which showed that PTGS2 inhibitors have a positive effect on the prognostic survival of patients with colorectal cancer. Other researchers have shown that PTGS2 expression in colon tissue increases prostaglandin synthesis, which can cause visceral hypersensitivity in patients with irritable bowel syndrome [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Song et al [ 31 ] showed that reducing PTGS2 expression can help to reduce the occurrence of colorectal cancer. This possibility is consistent with the results presented by Venè et al [ 32 ], which showed that PTGS2 inhibitors have a positive effect on the prognostic survival of patients with colorectal cancer. Other researchers have shown that PTGS2 expression in colon tissue increases prostaglandin synthesis, which can cause visceral hypersensitivity in patients with irritable bowel syndrome [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…The expression levels of TAC1, PTGS2 and FGF1 in resected specimen of NB patients with or without metastasis were then validated by qRT-PCR. Although the expression of TAC1, PTGS2 and FGF1 were related with many kinds of tumorigenesis, such as non-small cell lung cancer, pancreatic ductal cancer, colorectal cancer, squamous cell carcinoma, gastric cancer and clear cell renal cell carcinoma [26][27][28][29][30][31][32][33], but these genes expression did not exhibit significant change as expected as the microarray results, indicating that these three genes may not the pivotal gene that participate in the metastasis of NB.…”
Section: Discussionsupporting
confidence: 50%
“…For example, among these genes we found PTGS2. This gene has been associated with inflammatory stimuli and expressed in tumor cells of colorectal cancer [49, 50]. Another example is VEGF-A, a gene that encodes an angiogenic factor that has been detected up-regulated in different types of tumors such as colorectal cancer [51, 52].…”
Section: Discussionmentioning
confidence: 99%